Nonexistence results of solutions to systems of semilinear differential inequalities on the Heisenberg group - Abdallah El Hamidi; Mokhtar Kirane (Abstract and Applied Analysis)
We establish nonexistence results to systems of differential inequalities on the (2N+1)-Heisenberg group. The systems considered here are of the type (ESm). These nonexistence results hold for N less than critical exponents which depend on pi and γi, 1≤i≤m. Our results improve the known estimates of the critical exponent.